INFLUENCE OF HIKING IN SPORTS CLASSES IN UNWE ON STUDENTS ATTITUDES TOWARDS THE NATURE - V. Jordanov; Zh. Georgiev; E. Jordanov (Trakia Journal of Sciences)
The problems of pollution and the destruction of nature have been a part of us for a long time. No matter how much people are interested and trusted in all the threatening forecasts, no one can deny the tremendous changes that have taken place in our environment over the last century. Addressing these problems is one of the major tasks of future generations. The study aims to track the impact of hiking as a possible sport at UNWE on students' attitudes toward nature protection. The study involved 229 students enrolled in various sports at the university, divided into two groups. The experimental group (161) - including students walking in the mountains and the control group (68) - including students attending other sports at UNWE. Both surveys were conducted at the beginning and end of the school year, using the "Questionnaire of the attitude towards the protection of nature". The results show that the students who participated in the hiking activities in the mountains increase statistically significantly the actions they take to protect nature. No such changes are observed in students from other sports. In terms of knowledge, there are no significant changes in both groups.